2008
DOI: 10.4103/0019-5359.44483
|View full text |Cite
|
Sign up to set email alerts
|

Dapsone, danazol, and intrapartum splenectomy in refractory ITP complicating pregnancy

Abstract: Currently there is no consensus on the treatment of refractory idiopathic thrombocytopenic purpura (ITP) complicating pregnancy. Our patient with chronic ITP complicating pregnancy, who was refractory to steroids, dapsone, and danazol, was treated successfully with intrapartum splenectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Multiple case reports about the use of dapsone in a variety of diseases support the assumption of innocuousness. [39, 50, 76, 97, 105, 106, 109, 154, 158]. In any case, the risk of not treating the mother must be weighed up against the risk for the fetus.…”
Section: Conclusion For Treating Patients With Dapsonementioning
confidence: 99%
“…Multiple case reports about the use of dapsone in a variety of diseases support the assumption of innocuousness. [39, 50, 76, 97, 105, 106, 109, 154, 158]. In any case, the risk of not treating the mother must be weighed up against the risk for the fetus.…”
Section: Conclusion For Treating Patients With Dapsonementioning
confidence: 99%
“…10 The acceptable safety profile of dapsone has been previously reported in several articles. 9,[11][12][13] Several studies have reported that dapsone is an effective drug regardless of previously used treatments. The study by Zaja et al 11 in 20 patients reported a response rate of 55% and a complete response rate of 20%, Damodar et al 13 found a response rate of 61.8% and a complete response rate of 48% in 55 patients, and Colella et al 14 reported a response rate of 66% and a complete response rate of 24% in 122 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, the success of this therapeutic option for treating refractory thrombocytopenia in various conditions, such as ITP, systemic lupus erythematosus, and primary antiphospholipid syndrome, was reported in a string of case reports . In some of these reports, it was successfully used in children, HIV‐positive patients, the elderly, and pregnant women .…”
Section: Reviewmentioning
confidence: 99%